Acute stimulation with symmetric biphasic pulses induces less ataxia compared to cathodic pulses in DBS for essential tremor - Boogers, Alexandra; Peeters, Jana; Van Bogaert, Tine; Rusz, Jan; Bogaert-Miclaus, Camelia; Loret, Griet; De Vloo, Philippe; Vandenberghe, Wim; Nuttin, Bart; Mc Laughlin, Myles (Parkinsonism & related disorders, 2023)
BACKGROUND: Symmetric biphasic pulses have been shown to acutely increase the therapeutic window of ventralis intermedius deep brain stimulation (Vim-DBS) for essential tremor (ET) compared to cathodic pulses. Acute supratherapeutic stimulation can induce ataxic side effects in Vim-DBS. OBJECTIVE: To investigate the effect on tremor, ataxia and dysarthria of 3 h of biphasic stimulation in patients with DBS for ET. METHODS: A randomized, doubled-blind, cross-over design was used to compare standard cathodic pulses with symmetric biphasic pulses (anode-first) during a 3-h period per pulse shape. During each 3-h period, all stimulation parameters were identical, except for the pulse shape. Tremor (Fahn-Tolosa-Marin Tremor Rating Scale), ataxia (International Cooperative Ataxia Rating Scale) and speech (acoustic and perceptual measures) were assessed hourly during the 3-h periods. RESULTS: Twelve ET patients were included. During the 3-h stimulation period, tremor control was equivalent between the two pulse shapes. Biphasic pulses elicited significantly less ataxia than cathodic pulses (p = 0.006). Diadochokinesis rate of speech was better for the biphasic pulse (p = 0.048), but other measures for dysarthria were not significantly different between the pulses. CONCLUSION: Symmetric biphasic pulses induce less ataxia than conventional pulses after 3 h of stimulation DBS in ET patients.
Keywords: ataxie; Essential Tremor; Ventral Thalamic Nuclei; Essential tremor; výsledek terapie; hluboká mozková stimulace; Deep Brain Stimulation; Dysarthria; dysartrie; Biphasic stimulation; Pulse shapes; tremor; Humans; Tremor; nuclei ventrales thalami; Deep brain stimulation; esenciální tremor; elektrody; Treatment Outcome; Electrodes; Ataxia; lidé